Computer anxiety and its correlates : a meta-analysis - Chua, Siew Lian. (2008)
This dissertation reviewed studies regarding computer anxiety published in the 1990s. The review focused on three main areas: (a) the nature of computer anxiety, (b) the existence of computer anxiety, and (c) the relationships between computer anxiety and its three correlates, namely, gender, age and computer experience.